Pengaruh Panhisterektomi dan Konsumsi Suplemen 1,25-Dihidroksivitamin D3 Selama 1,5 Bulan terhadap Retensi Kalsium pada Tikus Wistar - -, Hartiningsih; Anggraini, Devita; Widiyono, Irkham (Jurnal Veteriner; Vol 11 No 1 (2010))
The objective of the research was to study the effect of panhisterectomy and 1,25-dihydroxyvitamin D3supplement consumption for 1.5 months on Ca retention of Wistar rats fed with casein. Twenty female ofWistar rats, 8 weeks of age were randomly divided into four groups (normal group N and NK,panhisterectomized group H and HK) in wich group consisted of 5 rats. Group N and H rats were fed witha standard diet, while group NK and HK rats were fed with a standard diet+1,25-dihydroxyvitamin D3supplement. At 19 weeks of age, they were placed into individual metabolic cages for balance studies.From day 7 to 11 of the balance studies, daily unconsumed food, urine, and feces were collected andrecorded for Ca analyses. The research results showed that Ca comsumption and fecal Ca excretion weresignificantly higher (P<0.05) in panhisterectomized rats consuming 1,25-dihydroxyvitamin D3 supplement,as compared with the normal rats consuming 1,25-dihydroxyvitamin D3 supplement. Urinary Ca excretionand Ca retention in panhisterectomized rats were not significantly different those of normal rats. WhileCa consumption and fecal Ca excretion were significantly reduced (P<0.05) in normal rats consuming 1,25-dihydroxyvitamin D3 supplement but urinary Ca excretion and Ca retention in normal rats consuming1,25-dihydroxyvitamin D3 supplement were not significantly different compare with normal rats notconsuming 1,25-dihydroxyvitamin D3 supplement. It is evident that panhisterectomy and 1,25-dihydroxyvitamin D3 supplement did not affect the calcium retention.
Keywords: panhisterectomized, 1,25-dihydroxyvitamin D3, Ca retention Tongku Nizwan Siregar1, Teuku Armansyah2, Arman Sayuti3 dan Syafruddin3